2016
DOI: 10.1186/s12986-016-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in prevention and treatment of obesity: a critical view

Abstract: The worldwide prevalence of obesity more than doubled between 1980 and 2014. The obesity pandemic is tightly linked to an increase in energy availability, sedentariness and greater control of ambient temperature that have paralleled the socioeconomic development of the past decades. The most frequent cause which leads to the obesity development is a dysbalance between energy intake and energy expenditure. The gut microbiota as an environmental factor which influence whole-body metabolism by affecting energy ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
185
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(207 citation statements)
references
References 82 publications
7
185
0
15
Order By: Relevance
“…It was also described that some probiotic strain can improve these values near to the non-obese control [39]. In our study, the analysis of the glucose, cholesterol, LDL, HDL and triglycerides values showed increases in the obese control for 30 days and 60 days in relation to the normal control.…”
Section: Resultsmentioning
confidence: 63%
“…It was also described that some probiotic strain can improve these values near to the non-obese control [39]. In our study, the analysis of the glucose, cholesterol, LDL, HDL and triglycerides values showed increases in the obese control for 30 days and 60 days in relation to the normal control.…”
Section: Resultsmentioning
confidence: 63%
“…Применение пробиотиков и пребиотиков для улучшения взаимодействия между кишечными микроорганизмами и обменом веществ хозяина при ожирении и других метаболических заболе-ваниях широко исследовано [49].…”
Section: терапевтический потенциал манипулирова-ния кишечной микробиоunclassified
“…Akkermansia muciniphila has proved novel mechanism of action governing beneficial effects for obesity. [18,19].…”
Section: VIIImentioning
confidence: 99%